Projection of Sensitive Reality into Cellular Topology - Maurice, Olivier; Reineix, Alain; Durand, Philippe; Dubois, François; Beaussart, Eric (Acta Europeana Systemica, 2020)
The purpose of this paper is to discuss about the abstract representation of some reality in a given referential into a cellular topology[1]. From this projection, tensorial algebra can then be employed to translate mathematically the behavior of this perceptible reality[2]. The first discussion wears on an experience realized on some object. We speak firstly of the perception of the object. How it can be seen, identified depending on various point of views. It fixes the reference frame where the observation is made. In this reference frame, environment involves domains for which parameters are defined: temperature, pressure, etc. A stimulus can be applied on known conditions in this environment and defined observable can be measured. From this pragmatic but stilling complex experience, a law can be extracted giving a relation between the stimulus and the observable. This law can be seen as a function, part of a non-linear metric when the same object is enclosed in a larger system[3]. Conditions on the domains and experiences must be detailed in order to control the system behavior, but masked parameters can influence the evolution of the system, being possible explanations for emergences. The whole system is modeling using “gamma matrices”, transformers and “tenfolds”.